Crossing the “Theory-practice Divide”: Learning to Be(come) a Teacher - Sarah Gravett (South African Journal of Childhood Education, 2012)
A common view of theory and practice as domains is that it is difficult, if not impossible, to traverse the epistemological chasm between them. After all, theories are ways of organising our world abstractly in ideas and concepts. Practice is the world that we inhabit empirically. It is a tangible world that we can see, feel, act on, act in, and so on. So, how can one even begin to argue that these apparently disparate worlds can be unified or that they are in the first instance not separate at all? My stance on this is that we, the educators of teachers, are party to the separation. In fact, we teach students that they should ‘apply’ theory to practice. Working with our own struggle at the university where I am based, I will argue that there may be ways of opening the borders between what is, on the one hand a philosophical question, and on the other, a purely empirical question. How do we teach and how do we teach the doing of teaching? My argument explores one way we might begin to restore; to whatever extent this is possible, the unity of theory and practice in teacher education.